Co-designing a conceptual controlled environment agriculture (CEA) model inside an Australian maximum-security prison: A research framework - S Vaughan; Christian Tietz; Mariano Ramirez (Cogent Social Sciences)
This research paper presents the framework for a research study that aims to define and evaluate the design requirements and the related feasibility of a controlled environment agriculture (CEA) system concept within a maximum-security prison in Australia. A co-design methodology will guide the study so that the views of a broad range of stakeholders can contribute to the conceptualization of a CEA farm system that is appropriately suited to correctional settings. The unique aspect of this research lies in the application of a bottom-up consultative process involving both prison administrators and inmates. Stakeholders will initially be asked to consider what CEA typology would be most suitable for a prison environment and then use this as a basis for developing a more extensive system design. As open-field agriculture represents a lower-cost alternative to CEA, this will also be considered to complement CEA. The co-design sessions will run in tandem with current growth trials of lettuce within the prison environment using different growing environments. The research is aimed at assisting to reduce the impacts of climate change, by growing produce locally. Growing produce within the prison walls reduces food miles and improves the nutritional quality of produce, which benefits longer-term inmate health. Growth trials that complement the co-design study are aimed at evaluating the ease of use for each of type growing environment. This research contributes significant new knowledge for the application of co-design in prisons, aimed at developing implementation guidelines for a CEA ecosystem that would supply fresh vegetables to pre-cooked inmate meals. The researcher has a unique perspective as an inmate. Outside community groups wishing to try CEA may also benefit from this study.